(3GdQbGHI GdHQdeGfjI Ydi CYeGd GdMcheI aj OhdI bWQ (B: s (3OQGSI ebGQfI (B/ s - (3Qje YHO GdQMef GdeSdeGfjs; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3Jcef GdZGjI ef gPG GdHMK ai eMGhdI Gdhbha Ydi GdGMcGe GdbGfhfjI HTGf GdQbGHI GdHQdeGfjI Ydi GYeGd GdSdWI GdJfajPjI ai OhdI bWQ ef NdGd GdfUhU GdOSJhQjI hGddGFMI GdOGNdjI GdMGdjI deLdS GdThQi GedG Gf Jchf gPg GdeMGhdI GdeJhGVYI dHfI ai GdecJHI GdYQHjI Ydi eSJhi GdHMK ai eLGd GdQbGHI GdHQdeGfjI Ydi GYeGd GdMcheIs
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2008.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B292 - 303.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdGbJQGM HQZHIs; (3WdH GdEMGWIs; (3GdJMbjb GdHQdeGfjs; (3GdGSJLhGHs; (3dLGf GdJMbjbs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs